Description of neonate of the freckled sand skate Psammobatis lentiginosa and observations on incubation period (Revista de Biología Marina y Oceanografía, 2022)
Some of the characters used in description and identification keys for skates are mostly valid for adults, and may dramatically change through ontogeny. The lack of morphological description of the neonate stage prevents from identifying them in nature. Two neonates of Psammobatis lentiginosa born in captivity and three collected from the wild were used in this study. Morphometric differences were found, among neonates, juveniles and adults, especially, in distance between orbits, distance between first gill slits and epichordal lobe. Colour pattern and spinulation presented differences as well. Observations on incubation period were taken. Hatching occurred 130 days after egg case collection.